Turnover intention among the navy people: the role of work family interference and organizational commitment / Muhamad Zafran Whab and Raida Abu Bakar - Whab, Muhamad Zafran; Abu Bakar, Raida (Universiti Teknologi MARA, 2021)
Human capital is a critical component of any organization's competitiveness. The absence of a high-capacity employee can have a negative impact on operational performance. The researcher examined the significance of organizational commitment as a mediator between work-family interference and turnover intention in the Royal Malaysian Navy. Data were collected from 400 navy personnel at the Lumut Naval Base in Perak, Malaysia, using structured questionnaires. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to analyze the data. Organizational commitment serves as a mediator between work-family interference and turnover intention in the Royal Malaysian Navy. According to the findings of this study, organizational commitment mediated the relationship between work-family interference and turnover intention. Additionally, work-family interference is a significant predictor of intention to leave the RMN.